Analisis benchmarking dalam menilai dan meningkatkan kinerja lingkungan industri pupuk - Mohamad Marzuki; Tri B. Prasetyo; Arie S. Utami (Jurnal Teknik Industri dan Manajemen Rekayasa, 2024)
PT. Pupuk Kujang is a company participating in PROPER committed to prioritizing environmental management in its operational activities. As evidence, periodic environmental performance measurements are necessary. This study aims to determine the level of success in environmental management and compliance with PROPER requirements. Benchmarking methods are used to determine PT. Pupuk Kujang's environmental performance ranking in 2021 compared to similar companies on a national, Asian, and international scale. Data collection was conducted through interviews and observations. The analysis results show that out of 10 aspects of environmental management, there are 4 aspects ranked in the top 25% nationally, 4 aspects ranked in the top 25% in Asia, 4 aspects ranked in the top 25% internationally, 4 aspects ranked at the 50% average nationally, 3 aspects ranked at the 50% average in Asia, 3 aspects ranked at the 50% average internationally, 2 aspects ranked in the bottom 25% nationally, 1 aspect ranked in the bottom 25% in Asia, and 1 aspect in high biodiversity. PT. Pupuk Kujang can implement sustainable development plans by optimizing steam consumption using Advanced Process Control (APC) technology and reducing high-pressure steam releases for energy efficiency.